Arabization of Neologisms in the Context of Technological Innovations in Light of the Dominance of Foreign Languages: Challenges, Opportunities and Strategies - Awadh, Awadh Nasser; Almansoob, Najeeb Taher (International Journal of Linguistics and Translation Studies, 2025)
The Arab world has a rich history of scientific and technological contributions, yet, it has faced challenges in maintaining its competitive edge in these fields. The Arabization of technology represents a vital step to bridge the gap between global innovations and local needs. This research seeks to explore the Arabization of innovations and neologisms, focusing on the challenges and opportunities that emerge during this process. It also determines the strategies used for Arabizing generally and Arabizing of neologisms particularly. To achieve these objectives, the researchers employed both analytical and descriptive methods, including the development of two data collection instruments: a questionnaire and interviews. The questionnaire focused on challenges of Arabization of neologisms. Additionally, it was distributed to 40 scholars, university professors, and translation experts to identify such challenges. The challenges were classified into several categories related to linguistic and cultural issues, Neologisms themselves, Mass media, Strategies, Arab academies and Dominance of foreign languages. Addressing these challenges requires collaboration among linguists, educators, and experts to create effective strategies for Arabizing neologisms. Developing standardized guidelines and fostering public acceptance will be crucial in enhancing the Arabization process. On the other hand, interviews were conducted with 10 experts to determine strategies used in Arabizing neologisms and shed light on the opportunities to activate the Arabization movement. Finally, various statistical tests were performed on the collected data to derive meaningful insights.